Computed Tomography-Guided Cryoablation of Local Recurrence after Primary Resection of Pancreatic Adenocarcinoma - Pusceddu, Claudio (Clin Pract, 2015)
The optimal management of local recurrences after primary resection of pancreatic cancer still remains to be clarified. A 58-year-old woman developed an isolated recurrence of pancreatic cancer six year after distal pancreatectomy. Re-resection was attempted but the lesion was deemed unresectable at surgery. Then chemotherapy was administrated without obtaining a reduction of the tumor size nor an improvement of the patient’s symptoms. Thus the patient underwent percutaneous cryoablation under computed tomography (CT)-guidance obtaining tumor necrosis and a significant improvement in the quality of life. A CT scan one month later showed a stable lesion with no contrast enhancement. While the use of percutaneous cryoblation has widened its applications in patients with unresectable pancreatic cancer, it has never been described for the treatment of local pancreatic cancer recurrence after primary resection. Percutaneous cryoablation deserves further studies in the multimodality treatment of local recurrence after primary pancreatic surgery.